2020
DOI: 10.3389/fonc.2020.01416
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Nomogram for Prediction of Peritoneal Metastasis in Patients With Gastric Cancer

Abstract: The aim of this study is to evaluate whether radiomics imaging signatures based on computed tomography (CT) could predict peritoneal metastasis (PM) in gastric cancer (GC) and to develop a nomogram for preoperative prediction of PM status. Methods: We collected CT images of pathological T4 gastric cancer in 955 consecutive patients of two cancer centers to analyze the radiomics features retrospectively and then developed and validated the prediction model built from 292 quantitative image features in the train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Previous studies have revealed the diagnostic value of radiomics for PM in GC based on conventional CT derived radiomics, with AUCs in the range of 0.724 to 0.873 in the validation cohort (32)(33)(34). In our study, similar performance was also observed in the R_MIX model built by 120kV-equivalent…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have revealed the diagnostic value of radiomics for PM in GC based on conventional CT derived radiomics, with AUCs in the range of 0.724 to 0.873 in the validation cohort (32)(33)(34). In our study, similar performance was also observed in the R_MIX model built by 120kV-equivalent…”
Section: Discussionsupporting
confidence: 84%
“…Our results gained outbreaking progress compared with a previous study. According to the nomogram (AUC 0.90) in the training set and (AUC 0.88) in the validation set, the accuracy of the prediction was obviously higher than the investigation that was based on CT with an AUC of 0.75 (43). In contrast to CT, PET has better performance, which means metabolic parameters play an important role in the model.…”
Section: Discussionmentioning
confidence: 89%
“…Compared with the abovementioned studies, our nomograms have several improvements. First, most of the studies were focused on the survival status of whole patients with GC or AGC (10)(11)(12)(13)(14)(15)(16)18). Instead, we went a step further and focused on T4a GC in the subdivided perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram is a practical tool in medical practice, which could pictorially represent a multivariable model. Recently, nomograms mostly concentrate on the patients of early-stage or under single treatment, and they mostly adequate for prognosis predicting intraoperatively or postoperatively (10)(11)(12)(13)(14)(15)(16). However, there still few nomograms integrating all the relevant clinicopathologic characters for patients with T4a GC.…”
Section: Introductionmentioning
confidence: 99%